Combination of platelet-rich fibrin and calcium sulfate in socket augmentation / Tipu Sultan - Tipu, Sultan (2019)
Objectives: The aim of this clinical study was to evaluate and compare vertical, horizontal and volumetric dimensional changes of alveolar ridge using combinations of platelet-rich fibrin and calcium sulfate (PRF-CS) and platelet-rich fibrin and xenograft (PRF-X) in socket augmentation procedure. Materials and Methods: Ten subjects requiring single maxillary premolar tooth extraction were included. Five sockets received PRF-CS grafts and five sockets received PRF-X grafts. Stone cast models were used to assess the changes of soft tissue level. Cone beam computerized tomography (CBCT) images were produced to measure horizontal and vertical dimensions. The CBCT images were then exported into MIMICS software to analyze the bone volume. All measurements were recorded at baseline (before extraction) and at 5 months post-extraction. Results: Significant reduction in vertical and horizontal dimensions was observed in both the groups at 5 months post-extraction except for distal bone height (DBH) (p=0.094) and palatal bone height (PBH) (p=0.065) in PRF-X group. PRF-CS group demonstrated 12.2 % horizontal resorption as compared with 14.84% in PRF-X group (p>0.05). For PRFCS group, resorption for mesial bone height (MBH=19.58%), buccal bone height (BBH=18.87%) and palatal bone height (PBH=15.66%) was more than resorption for PRF-X (MBH=8.48%, BBH=7.26% and PBH=4.33%) (p>0.05). The bone volume reduction of 11.43% and 7.74% was observed in PRF-CS group and PRF-X group respectively (p>0.05). Conclusion: PRF-CS can be used as a graft material for socket augmentation procedure.